2020
DOI: 10.1177/0894486520938891
|View full text |Cite
|
Sign up to set email alerts
|

From Intention to Trust to Behavioral Trust: Trust Building in Family Business Advising

Abstract: By building on foundations from psychology, we aim to enhance academic understanding of the advising process in family businesses. We find evidence, based on rich qualitative data, suggesting that trust serves as a key construct in the relationship between family businesses and their advisors. In particular, we empirically show and theorize that trusting relationships evolve via a nonlinear process characterized by a constant interplay between cognitive and—increasingly important—affective assessments of famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 89 publications
(177 reference statements)
1
34
0
Order By: Relevance
“…The first paper is by De Groote and Bertschi-Michel (2020). The starting point of this study is that the emphasis on socioemotional wealth in family businesses informs some of their idiosyncratic decisions, including the assessment of external collaborations (Berrone, Cruz, Gomez-Mejia, & Larraza-Kintana, 2010).…”
Section: The Articles In This Second Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The first paper is by De Groote and Bertschi-Michel (2020). The starting point of this study is that the emphasis on socioemotional wealth in family businesses informs some of their idiosyncratic decisions, including the assessment of external collaborations (Berrone, Cruz, Gomez-Mejia, & Larraza-Kintana, 2010).…”
Section: The Articles In This Second Special Issuementioning
confidence: 99%
“…Second, they leverage their empathy to nourish family harmony and capture family business members’ attention to distinctive circumstances and scenarios. This latter effect relates to an affective basis defined as “the internal processing of emotions related to subtle feelings” (De Groote and Bertschi-Michel, 2020, p. 1, italics added). They also offer empirical evidence that a trusting relationship is related to cognitive and affective appraisals that persistently interact.…”
Section: The Articles In This Second Special Issuementioning
confidence: 99%
“…Furthermore, recent literature on the advising process in FBs (e.g., de Groote & Bertschi-Michel, 2021; Strike, 2013), although not specifically focused on strategy, has demonstrated the capacity of the advisors to build trust with family actors. Studies have shown that family actors are more accepting of the advisor’s influence when there are affective forms of trust (e.g., de Groote & Bertschi-Michel, 2021; Salvato & Corbetta, 2013; Strike, 2013), which grows with feelings of liking the advisor as “a good person” (de Groote & Bertschi-Michel, 2021, p. 143).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, to date, the ways in which such advisors can actually facilitate these interactions, thus affecting strategy work over time, remain unexplored. Given recent insights on advisors’ capacity to ease tensions between family actors and nonfamily managers (van Helvert-Beugels et al, 2020) as well as to build trustful relationships (de Groote & Bertschi-Michel, 2021; Strike, 2013), we argue that advisors could be those who create connections with (and between) the actors involved in this triad. These relational dynamics merit more investigation to delve into the micro-level activities of strategy work that could bring family actors and nonfamily managers closer.…”
Section: Introductionmentioning
confidence: 97%
“…Creating a trust learning environment could promote the educational core values of benevolence, honesty, loyalty, and openness to both achieve school targets and school learning outcomes (Weinstein, Raczynski, & Pena, 2020). If the school principals could create a trusted learning environment, the school stakeholders not only exchange their thoughts to achieve the school outcomes (Crane, 2020) but also build a strong friendship in leading school improvement and makes all school members feel secure (Groote & Bertschi-Michel, 2020), and increase school social reputation and enrollment rate . Therefore, the following literature review will cover the following themes: why trust is essential in YBR school; what benefits of creating trust between parents and school principal; the trust between teachers and principals for the quality of teaching, teachers sense of responsibility, and teaching evaluation; and trust between students and principals for student learning outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%